Ceramic core with enhanced whisker orientation and preparation method thereof
By metallizing the ceramic whiskers and applying a magnetic field during 3D printing, the orientation of composite powder in the ceramic core is solved, and the problem of poor whisker dispersion and thin part enhancement effect of the ceramic core is significantly Improves its bending strength and comprehensive performance at high temperature and room temperature.
Patent Information
- Application Number
- CN202411874416.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the poor whisker dispersion of the ceramic core and the poor reinforcement effect in thin areas lead to insufficient comprehensive performance stability and strength of the ceramic core, especially at high temperatures, showing poor bending strength.
By metallizing the ceramic whiskers, a composite powder with the core as ceramic whiskers and the shell as metal phase is formed, and a magnetic field is applied during the 3D printing photocuring and molding process to regulate the orientation of the composite powder and improve the ceramic core Mechanical properties.
The high-temperature bending strength and room-temperature bending strength of the ceramic core have been significantly improved, especially in thin areas with excellent strengthening effect, simple process, good dispersion and high bonding strength.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic core preparation, and in particular to a ceramic core with enhanced whisker orientation and a preparation method thereof. Background Art
[0002] With the development of the aviation industry, the temperature bearing capacity of the engine is increasingly required. This also puts forward higher requirements on the temperature bearing capacity of the blade, which is the core component of the engine. At present, simply improving the temperature bearing capacity of the blade material itself can no longer meet the growing high requirements of the engine for the high temperature resistance and high cooling efficiency of the blade. From the design point of view, improving the cooling channel of the blade to improve the temperature bearing capacity of the blade has become the main way. However, the design and manufacture of such a complex cooling channel requires that the ceramic core forming such a complex structure also has high comprehensive performance. As a transition part, the ceramic core must not only have high room temperature and high temperature strength to resist the impact of external forces and high temperature metal liquid, but also have high porosity or pore channels so that the stripping liquid can smoothly enter the core to remove it during the subsequent stripping process. However, high porosity or pore channels will inevitably sacrifice its strength. Especially for the complex cores currently designed, some parts of some cores are very thin, even less than 1mm. These positions are often the most prone to problems such as fracture, which seriously affects the overall manufacturing quality of the core. Therefore, it is necessary to design and develop a new strengthening strategy to enhance the performance of the ceramic core, especially its thin parts.
[0003] At present, a lot of research and development has been carried out on enhancing the performance of ceramic cores. For example, adding zirconium silicate to enhance the mechanical properties of the core is a common method, but due to the size of zirconium silicate and other reasons, the effect is not obvious in some thin parts. There are also ways to enhance the comprehensive performance of the core by adding nanoparticles, but the dispersion of nanoparticles is not easy to control, and the composition is too high, so the performance stability of the formed ceramic core is poor. One-dimensional whisker or fiber reinforcement is an effective way. Studies have shown that the introduction of whiskers into ceramic cores can improve their room temperature and high temperature mechanical properties to a certain extent. However, there are also problems with the introduction of whiskers. The whiskers will also be entangled, resulting in poor dispersion, affecting the local performance of the ceramic core. At the same time, the introduction of whiskers will cause the solid content of the ceramic core matrix to decrease, which will also affect its comprehensive performance. Therefore, new whisker introduction strategies need to be developed to solve the current problems, in order to prepare high-performance ceramic cores, especially to improve the comprehensive performance of thin core parts.
[0004] Traditional ceramic core preparation is mainly based on hot die casting, which requires high mold composition, long ceramic core manufacturing cycle and high cost. 3D printing technology can realize controllable printing of ceramic cores with complex structures through software program design, and it is highly efficient and can effectively avoid the defects of hot die casting ceramic cores. Therefore, seeking a new strengthening strategy in 3D printing photocuring ceramic cores to enhance the performance of ceramic cores, especially their thin parts, is of great significance for promoting the development of ceramic cores and the application of 3D printing technology in the field of ceramic cores.
[0005] The existing patent CN109365802A discloses a method for preparing a core-shell structured metal-ceramic composite powder, which comprises placing ceramic powder particles in a reactor, heating the reaction raw materials, using a carrier gas to carry the reaction raw material vapor into the reactor, introducing hydrogen to cause a reduction reaction, so that the catalytic metal is deposited on the surface of the ceramic powder particles; placing the ceramic powder particles in a reactor in a water bath, adding a metal salt raw material and a reducing agent, and coating a metal coating layer through an autocatalytic reaction to obtain a metal-ceramic composite powder.
[0006] The existing patent CN118515996A discloses a silicon carbide whisker directional reinforced wear-resistant and friction-reducing phosphate ceramic coating and a preparation method thereof. The coating material comprises the following components in mass fraction: 1-5wt% magnetic silicon carbide whisker, 2wt% curing agent, 50.5wt% phosphate binder, and 42.5-47.5wt% aggregate aluminum oxide. The present invention adopts a hydrothermal synthesis method to prepare magnetic silicon carbide whiskers, and then mixes with aluminum oxide, zinc oxide and phosphate binder to obtain a coating, and finally applies the composite coating on the surface of a metal substrate, and uses a magnetic field auxiliary effect to control the arrangement direction of the silicon carbide whiskers during the curing process, so as to obtain a silicon carbide whisker directional reinforced wear-resistant and friction-reducing phosphate ceramic coating.
[0007] In summary, the above two existing patents have not solved the problems in the prior art regarding the dispersion of whiskers and the poor reinforcement effect on the thin parts of the ceramic core. Summary of the invention
[0008] Based on the above technical problems, the present invention proposes a ceramic core with enhanced whisker orientation and a preparation method thereof, which solves the problems in the prior art regarding the dispersion of whiskers and the poor reinforcement effect on the thin parts of the ceramic core.
[0009] To achieve the above object, the present invention proposes a ceramic core with enhanced whisker orientation and a preparation method thereof. The specific technical scheme is as follows:
[0010] A method for preparing a ceramic core with enhanced whisker orientation, the method comprising the following steps:
[0011] S1, preparing a composite powder with a core of a ceramic whisker and a shell of a metal phase;
[0012] S2, mixing refractory powder and composite powder to form ceramic core slurry;
[0013] S3, using ceramic core slurry to form a ceramic core blank and adjust the powder orientation;
[0014] S4, embedding the ceramic core blank with powder and then sintering at high temperature to obtain a ceramic core;
[0015] In step S2, the weight percentage of the refractory powder is 50-70%, and the weight percentage of the composite powder is 1-10%;
[0016] In step S3, a ceramic core blank is obtained by 3D printing photocuring, and a magnetic field is applied during the 3D printing process;
[0017] The magnetic field strength of the magnetic field is 0.1-2T.
[0018] Furthermore, in step S1, the ceramic whiskers are metallized, and then a composite powder having a core of the ceramic whiskers and a shell of the metal phase is prepared by a chemical plating method.
[0019] Furthermore, in step S1, a chemical plating solution is prepared, and the treated ceramic whiskers are added into the chemical plating solution for ultrasonic chemical plating to obtain a composite powder having a ceramic whisker core and a metal phase shell.
[0020] Further, in step S1, a sulfate solution is added to deionized water, and then a reducing agent and a complexing agent are added to obtain a chemical plating solution;
[0021] The metal element in the sulfate solution is nickel, cobalt or copper, and the added ratio of the sulfate solution is 20-40%;
[0022] The added amount of the ceramic whisker accounts for 10-30% by weight of the total amount. The ceramic whisker is alumina whisker, zirconia whisker, mullite whisker, silicon nitride whisker or silicon carbide whisker. The diameter of the ceramic whisker is 50-500nm, the length is 1-10μm, and the purity is not less than 90%.
[0023] Furthermore, in step S2, refractory powder and composite powder are added into the photocurable resin and uniformly dispersed to obtain ceramic core slurry.
[0024] Furthermore, the refractory powder is quartz glass powder, alumina powder, magnesium oxide powder, calcium oxide powder or yttrium oxide powder, and the particle size of the refractory powder is 10-40 μm and the purity is not less than 99.90%.
[0025] Furthermore, the power of the 3D printing light-stereolithography is 5-20 mW / cm 2The thickness of each layer is 50-500μm, and the exposure time of each layer is 1-10s.
[0026] Furthermore, in step S3, the magnetic field strength of the magnetic field is 1-2T.
[0027] Furthermore, in step S4, the final sintering temperature of the high temperature sintering is 1500-1600°C;
[0028] The heating process of high temperature sintering includes multiple heating stages, the heating range of each heating stage is 400-600°C, the heating rate is 2-8°C / min, and the insulation time after heating in each stage is 2-10h;
[0029] The multiple heating stages include: the first stage is heating from room temperature to 400°C at a heating rate of 2°C / min, and keeping at 400°C for 3 hours; the second stage is heating from 400°C to a maximum temperature of 900°C at a heating rate of 5°C / min, and keeping at this temperature for 5 hours; the third stage is heating from 900°C to a maximum temperature of 1500°C at a heating rate of 8°C / min, and keeping at this temperature for 10 hours.
[0030] The present invention also provides a whisker-oriented enhanced ceramic core, which is prepared using the method for preparing the whisker-oriented enhanced ceramic core.
[0031] Based on the above technical solution, the present invention has at least the following beneficial effects:
[0032] 1. The present invention proposes a ceramic core with enhanced whisker orientation and a method for preparing the same. The introduced ceramic whiskers are surface treated to achieve metallization, and a composite powder with a core of ceramic whiskers and a shell of a metal phase is prepared by a chemical plating method. The coating of the metal phase can effectively improve the dispersibility of the ceramic whiskers.
[0033] 2. The present invention proposes a ceramic core with enhanced whisker orientation and a preparation method thereof. During the 3D printing process of the ceramic core, a magnetic field is applied to effectively realize the oriented arrangement of a composite powder with a core of ceramic whiskers and a shell of a metal phase. Especially in the thin parts of the ceramic core, its mechanical properties can be effectively improved through whisker orientation.
[0034] 3. The invention proposes a whisker-oriented reinforced ceramic core and a preparation method thereof, which has a simple preparation process, good whisker dispersion, high whisker-matrix bonding strength, and excellent strengthening effect on the performance of the ceramic core, especially the thin zone.
[0035] 4. The whisker-oriented enhanced ceramic core and its preparation method proposed in the present invention can be applied to the development and application of ceramic cores of other systems. DETAILED DESCRIPTION
[0036] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0037] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0038] In order to solve the problems of whisker dispersion and poor reinforcement effect on thin parts of ceramic cores in the prior art, the present invention provides a whisker-oriented reinforced ceramic core and a preparation method thereof.
[0039] To achieve the above-mentioned purpose, the present invention proposes a ceramic core with enhanced whisker orientation and a preparation method thereof. First, the ceramic whiskers are metallized and a composite powder with a core of ceramic whiskers and a shell of metal phase is formed by a chemical plating method. Then, during the 3D printing light curing process, a magnetic field is applied to control the orientation of the composite powder, thereby achieving the enhancement of the comprehensive performance of the ceramic core.
[0040] A method for preparing a ceramic core with enhanced whisker orientation proposed by the present invention specifically comprises the following steps:
[0041] S1, preparing a composite powder with a core of a ceramic whisker and a shell of a metal phase;
[0042] Specifically, the ceramic whiskers are metallized, and a composite powder with a core of ceramic whiskers and a shell of a metal phase is prepared by a chemical plating method. The metal phase component is one of nickel, cobalt, and copper, and is added to deionized water in the form of nickel sulfate, cobalt sulfate, and copper sulfate, and the addition ratio is 20-40%, and then a reducing agent and a complexing agent are added to obtain a chemical plating solution; the ceramic whiskers are dispersed in the chemical plating solution after electroplating treatment, and then subjected to ultrasonic chemical plating treatment, and then centrifugal treatment and drying treatment are performed to obtain a composite powder with a core of ceramic whiskers and a shell of a metal phase. The time of chemical plating treatment is 10-60 minutes.
[0043] In the chemical plating method, the weight percentage of the added ceramic whisker is 10-30% of the total amount. The ceramic whisker is one of aluminum oxide whisker, zirconium oxide whisker, mullite whisker, silicon nitride whisker or silicon carbide whisker. The diameter of the ceramic whisker is 50-500nm, the length is 1-10μm, and the purity is ≥90%.
[0044] S2, mixing refractory powder and composite powder to form ceramic core slurry;
[0045] Specifically, refractory powder and composite powder are added to the photocurable resin in proportion, and the refractory powder and composite powder are evenly dispersed in the photocurable resin by planetary ball milling to form a ceramic core slurry. The weight percentage of refractory powder in the ceramic core slurry is 50-70%, the weight percentage of composite powder in the ceramic core slurry is 1-10%, the speed of planetary ball milling is 100-250rpm / min, and the ball milling time is 10-24h.
[0046] The refractory powder is one of quartz glass powder, alumina powder, magnesium oxide powder, calcium oxide powder or yttrium oxide powder; the particle size of the refractory powder is 10-40 μm and the purity is ≥99.90%.
[0047] S3, using ceramic core slurry to form a ceramic core blank and adjust the powder orientation;
[0048] Specifically, the mixed ceramic core slurry is placed in a slurry tray of a 3D printer, and a ceramic core blank is obtained by 3D printing and photocuring. At the same time, a magnetic field is applied during the 3D printing process to regulate the orientation of the composite powder.
[0049] The power of the above 3D printing light-stereolithography is 5-20mW / cm 2 , the layer thickness is 50-500μm, the exposure time of each layer is 1-10s; the applied magnetic field strength is 0.1-2T.
[0050] S4, embedding the ceramic core blank with powder and then sintering at high temperature to obtain the ceramic core.
[0051] Specifically, after the ceramic core blank is buried, high-temperature sintering is performed to finally obtain a ceramic core with enhanced whisker orientation.
[0052] The final sintering temperature of the high temperature sintering is 1500-1600°C. The heating process of the high temperature sintering includes multiple heating stages. The heating range of each heating stage is 400-600°C, the heating rate is 2-8°C / min, and the insulation time after each stage of heating is 2-10h.
[0053] The method for preparing a ceramic core with enhanced whisker orientation proposed by the present invention is described below in conjunction with specific data values.
[0054] Example 1
[0055] S1. preparing a composite powder with a core of a ceramic whisker and a shell of a metal phase: firstly dissolving copper sulfate in deionized water at a ratio of 30%, and then sequentially adding a reducing agent, hypophosphite, and a complexing agent, citric acid, to obtain a chemical plating solution;
[0056] The zirconium oxide whiskers are subjected to a coarsening-sensitization-activation process, and then dispersed in a chemical plating solution for ultrasonic chemical plating. The weight percentage of the zirconium oxide whiskers added is 10%, and the ultrasonic chemical plating time is 30 minutes. The plated solution is then centrifuged, and the obtained precipitate is dried at 120°C to obtain a composite powder with a core of zirconium oxide whiskers and a shell of copper.
[0057] S2. According to the weight percentage, 50% of quartz glass powder with a particle size of 10 μm and 5% of composite powder are added to the liquid polyacrylate photocurable resin, and the quartz glass powder and the composite powder are evenly dispersed in the liquid polyacrylate photocurable resin by planetary ball milling to form a ceramic core slurry. The planetary ball milling speed is 200 rpm / min, the ball milling time is 20 hours, the ball-to-material ratio is 2:1, and after the ball milling is uniform, it is sieved through a 100-mesh screen to obtain a photocurable ceramic core slurry;
[0058] S3. Place the mixed ceramic core slurry in the slurry tray of the 3D printer and set the 3D printing parameters. The light curing power is 8 mW / cm 2 , the layer thickness is controlled to be 50 μm, the exposure time of each layer is 4 s, and the applied magnetic field power is turned on at the same time, the magnetic field strength is 0.1 T, and the magnetic field is applied during the printing process to obtain a ceramic core blank with enhanced ceramic whisker orientation.
[0059] S4. After the ceramic core blank is filled with calcined alumina powder as filler, the first stage is from room temperature to 500°C at a heating rate of 2°C / min, and it is kept at 500°C for 2 hours. The second stage is from 500°C to 1000°C at a heating rate of 5°C / min, and it is kept at this temperature for 5 hours. The third stage is from 1000°C to 1550°C at a heating rate of 8°C / min, and it is kept at this temperature for 10 hours. After cooling in the furnace, the ceramic core is finally obtained.
[0060] The core-shell structure composite powder in the ceramic core prepared in this embodiment is oriented along a certain direction, and the maximum room temperature flexural strength of the core perpendicular to the oriented direction is 42 MPa, and the maximum high temperature strength of the core at 1500° C. is 56 MPa.
[0061] Example 2
[0062] S1. Prepare a composite powder with a core of ceramic whiskers and a shell of a metal phase: first, dissolve copper sulfate in deionized water at a ratio of 25%, and then add a reducing agent, hypophosphite, and a complexing agent, citric acid, in sequence to obtain a chemical plating solution;
[0063] The aluminum oxide whiskers are subjected to a coarsening-sensitization-activation process, and then dispersed in a chemical plating solution for ultrasonic chemical plating. The weight percentage of aluminum oxide whiskers added is 30%, and the ultrasonic chemical plating time is 30 minutes. The plated solution is then centrifuged, and the obtained precipitate is dried at 120° C. to obtain a composite powder with an aluminum oxide whisker core and a copper shell.
[0064] S2. According to the weight percentage, 55% of magnesium oxide powder with a particle size of 15 μm and 9% of composite powder are added to the liquid polyacrylate photocurable resin, and the magnesium oxide powder and the composite powder are evenly dispersed in the liquid polyacrylate photocurable resin by planetary ball milling to form a ceramic core slurry. The planetary ball milling speed is 200 rpm / min, the ball milling time is 20 hours, the ball-to-material ratio is 2:1, and after the ball milling is uniform, it is sieved through a 100-mesh screen to obtain a photocurable ceramic core slurry;
[0065] S3. Place the mixed ceramic core slurry in the slurry tray of the 3D printer and set the 3D printing parameters. The light curing power is 10 mW / cm 2 , the layer thickness is controlled to be 100 μm, the exposure time of each layer is 5 s, and the applied magnetic field power supply is turned on at the same time, the magnetic field strength is 1 T, and the magnetic field is applied during the printing process to obtain the ceramic core blank.
[0066] S4. After the ceramic core blank is filled with calcined alumina powder as filler, the first stage is from room temperature to 400°C at a heating rate of 2°C / min, and it is kept at 400°C for 4 hours. The second stage is from 400°C to 950°C at a heating rate of 5°C / min, and it is kept at this temperature for 6 hours. The third stage is from 950°C to 1550°C at a heating rate of 8°C / min, and it is kept at this temperature for 10 hours. After cooling in the furnace, the ceramic core is finally obtained.
[0067] The core-shell structure composite powder in the ceramic core prepared in this embodiment is oriented along a certain direction, and the maximum room temperature flexural strength of the core perpendicular to the oriented direction is 60 MPa, and the maximum high temperature strength of the core at 1500° C. is 75 MPa.
[0068] Example 3
[0069] S1. Prepare a composite powder with a core of ceramic whiskers and a shell of a metal phase: dissolve nickel sulfate in deionized water at a ratio of 20%, and then add a reducing agent, hypophosphite, and a complexing agent, citric acid, in sequence to obtain a chemical plating solution;
[0070] The silicon carbide whiskers are subjected to a coarsening-sensitization-activation process, and then dispersed in a chemical plating solution for ultrasonic chemical plating. The weight percentage of silicon carbide whiskers added is 20%, and the treatment time is 30 minutes. The plated solution is then centrifuged, and the obtained precipitate is dried at 120°C to obtain a composite powder with a core of silicon carbide whiskers and a shell of nickel.
[0071] S2. According to the weight percentage, 70% of yttrium oxide powder with a particle size of 15 μm and 1% of composite powder are added to the liquid polyacrylate photocurable resin, and the yttrium oxide powder and the composite powder are evenly dispersed in the liquid polyacrylate photocurable resin by planetary ball milling to form a ceramic core slurry. The planetary ball milling speed is 200 rpm / min, the ball milling time is 20 hours, the ball-to-material ratio is 2:1, and after the ball milling is uniform, it is sieved through a 100-mesh screen to obtain a photocurable ceramic core slurry;
[0072] S3. Place the mixed ceramic core slurry in the slurry tray of the 3D printer and set the 3D printing parameters. The light curing power is 9mW / cm 2 , the layer thickness is controlled to be 110μm, the exposure time of each layer is 4s, and the applied magnetic field power is turned on at the same time, the magnetic field strength is 0.6T, and the magnetic field is applied during the printing process to obtain the ceramic core blank.
[0073] S4. After the ceramic core blank is filled with calcined alumina powder as filler, the first stage is from room temperature to 500°C at a heating rate of 3°C / min, and it is kept at 500°C for 3 hours. The second stage is from 500°C to 1050°C at a heating rate of 5°C / min, and it is kept at this temperature for 5 hours. The third stage is from 1050°C to 1600°C at a heating rate of 8°C / min, and it is kept at this temperature for 8 hours. After cooling in the furnace, the ceramic core is finally obtained.
[0074] The core-shell structure composite powder in the ceramic core prepared in this embodiment is oriented along a certain direction, and the maximum room temperature flexural strength of the core perpendicular to the oriented direction is 58 MPa, and the maximum high temperature strength of the core at 1500° C. is 74 MPa.
[0075] Example 4
[0076] S1. Prepare a composite powder with a core of ceramic whiskers and a shell of a metal phase: dissolve copper sulfate in deionized water at a ratio of 40%, and then add a reducing agent, hypophosphite, and a complexing agent, citric acid, in sequence to obtain a chemical plating solution;
[0077] The mullite whisker is subjected to a coarsening-sensitization-activation process, and then dispersed in a chemical plating solution for ultrasonic chemical plating. The weight percentage of the mullite whisker added is 25%, and the treatment time is 30 minutes. The plated solution is then centrifuged, and the obtained precipitate is dried at 120° C. to obtain a composite powder with a core of mullite whisker and a shell of copper.
[0078] S2. According to the weight percentage, 65% of alumina powder with a particle size of 20 μm and 10% of composite powder are added to the liquid polyacrylate photocurable resin, and the alumina powder and the composite powder are evenly dispersed in the liquid polyacrylate photocurable resin by planetary ball milling to form a ceramic core slurry. The planetary ball milling speed is 200 rpm / min, the ball milling time is 20 hours, the ball-to-material ratio is 2:1, and after the ball milling is uniform, it is sieved through a 100-mesh screen to obtain a photocurable ceramic core slurry;
[0079] S3. Place the mixed ceramic core slurry in the slurry tray of the 3D printer and set the 3D printing parameters. The light curing power is 7 mW / cm 2 , the layer thickness is controlled to be 150μm, the exposure time of each layer is 4s, and the applied magnetic field power is turned on at the same time, the magnetic field strength is 2T, and the magnetic field is applied during the printing process to obtain the ceramic core blank.
[0080] S4. After filling the 3D printed complex ceramic core blank with calcined alumina powder as filler, the first stage is from room temperature to 500°C at a heating rate of 2°C / min, and kept at 500°C for 4 hours. The second stage is from 500°C to 1000°C at a heating rate of 5°C / min, and kept at this temperature for 5 hours. The third stage is from 1000°C to 1600°C at a heating rate of 8°C / min, and kept at this temperature for 8 hours. After cooling in the furnace, the ceramic core is finally obtained.
[0081] The core-shell structure composite powder in the ceramic core prepared in this embodiment is oriented along a certain direction, and the maximum room temperature flexural strength of the core perpendicular to the oriented direction is 67 MPa, and the maximum high temperature strength of the core at 1500° C. is 83 MPa.
[0082] Example 5
[0083] S1. Prepare a composite powder with a core of ceramic whiskers and a shell of a metal phase: dissolve cobalt sulfate in deionized water at a ratio of 35%, and then add a reducing agent, hypophosphite, and a complexing agent, citric acid, in sequence to obtain a chemical plating solution;
[0084] The silicon nitride whiskers are subjected to a coarsening-sensitization-activation process, and then dispersed in a chemical plating solution for ultrasonic chemical plating. The weight percentage of silicon nitride whiskers added is 26%, and the treatment time is 30 minutes. The plated solution is then centrifuged, and the obtained precipitate is dried at 120°C to obtain a composite powder with a core of silicon nitride whiskers and a shell of cobalt.
[0085] S2. According to the weight percentage, 60% of alumina powder with a particle size of 10 μm and 8% of composite powder are added to the liquid polyacrylate photocurable resin, and the alumina powder and the composite powder are evenly dispersed in the liquid polyacrylate photocurable resin by planetary ball milling to form a ceramic core slurry. The planetary ball milling speed is 200 rpm / min, the ball milling time is 20 hours, the ball-to-material ratio is 2:1, and after the ball milling is uniform, it is sieved through a 100-mesh screen to obtain a photocurable ceramic core slurry;
[0086] S3. Place the mixed ceramic core slurry in the slurry tray of the 3D printer and set the 3D printing parameters. The light curing power is 8.5 mW / cm 2 , the layer thickness is controlled to be 180μm, the exposure time of each layer is 4s, and the applied magnetic field power is turned on at the same time, the magnetic field strength is 1.5T, and the magnetic field is applied during the ceramic core printing process to obtain the ceramic core blank.
[0087] S4. After filling the 3D printed complex ceramic core blank with calcined alumina powder as filler, the temperature is raised from room temperature to 400°C at a rate of 2°C / min, and kept at 400°C for 3 h. The second stage is to heat from 400°C to a maximum temperature of 900°C at a rate of 5°C / min and keep warm for 5 h. The third stage is to heat from 900°C to a maximum temperature of 1500°C at a rate of 8°C / min and keep warm for 10 h.
[0088] The core-shell structure composite powder in the ceramic core prepared in this embodiment is oriented along a certain direction, and the maximum room temperature flexural strength of the core perpendicular to the oriented direction is 75 MPa, and the maximum high temperature strength of the core at 1500° C. is 89 MPa.
[0089] Comparative Example 1
[0090] S1. Prepare a composite powder with a core of ceramic whiskers and a shell of a metal phase: dissolve copper sulfate in deionized water at a ratio of 30%, and then add a reducing agent, hypophosphite, and a complexing agent, citric acid, in sequence to obtain a chemical plating solution;
[0091] The ceramic whiskers are subjected to a coarsening-sensitization-activation process, and then dispersed in a chemical plating solution for ultrasonic chemical plating for 30 minutes. The plated solution is then centrifuged and the resulting precipitate is dried at 120° C. to obtain a composite powder having a ceramic whisker core and a metal shell.
[0092] S2. According to the weight percentage, 55% of quartz glass ceramic powder with a particle size of 10 μm and 5% of composite powder are added to the liquid polyacrylate photocurable resin, and the ceramic powder and the composite powder are evenly dispersed in the liquid polyacrylate photocurable resin by planetary ball milling. The planetary ball milling speed is 200 rpm / min, the ball milling time is 20 hours, the ball-to-material ratio is 2:1, and after the ball milling is uniform, it is sieved through a 100-mesh screen to obtain a photocurable ceramic core slurry;
[0093] S3. Place the mixed ceramic core slurry in the slurry tray of the 3D printer and set the 3D printing parameters. The light curing power is 8 mW / cm 2 , the layer thickness was controlled to be 50 μm, the exposure time of each layer was 4 s, and no magnetic field was applied to obtain a ceramic core blank.
[0094] S4. After filling the 3D printed complex ceramic core blank with calcined alumina powder as filler, heat it from room temperature to 600 °C at a heating rate of 2 °C / min, keep it at 600 °C for 2 h, continue to heat it to the maximum temperature of 1250 °C at a heating rate of 5 °C / min, and keep it at this temperature for 2 h, finally obtaining the ceramic core.
[0095] The flexural strength of the ceramic core in Comparative Example 1 is 20 MPa at room temperature and 16 MPa at 1550°C.
[0096] Comparative Example 2
[0097] S1. According to the weight percentage, 55% of quartz glass ceramic powder with a particle size of 10μm and 5% of composite powder with a core of ceramic whiskers and a shell of metal phase (without chemical plating) are added to the liquid polyacrylate photocurable resin, and the ceramic powder and the composite powder are evenly dispersed in the liquid polyacrylate photocurable resin by planetary ball milling. The planetary ball milling speed is 200rpm / min, the ball milling time is 20h, the ball-to-material ratio is 2:1, and after uniform ball milling, the 100-mesh screen is sieved to obtain the photocurable ceramic core slurry;
[0098] S2. Place the mixed ceramic core slurry in the slurry tray of the 3D printer and set the 3D printing parameters. The light curing power is 8 mW / cm 2 , the layer thickness was controlled to be 50 μm, the exposure time of each layer was 4 s, and no magnetic field was applied to obtain a ceramic core blank.
[0099] S3. After filling the 3D printed complex ceramic core blank with calcined alumina powder as filler, heat it from room temperature to 600 °C at a heating rate of 2 °C / min, keep it at 600 °C for 2 h, continue to heat it to the maximum temperature of 1250 °C at a heating rate of 5 °C / min, and keep it at this temperature for 2 h, finally obtaining the ceramic core.
[0100] The flexural strength of the ceramic core in Comparative Example 2 is 20.15 MPa at room temperature and 18.52 MPa at 1550°C.
[0101] From the comparison of the results of the above-mentioned Examples 1-5 and Comparative Examples 1-2, it can be seen that the room temperature flexural strength and high temperature flexural strength of the ceramic core prepared according to the method of the present invention are greater than the results in the comparative examples, and the performance of the ceramic core is significantly improved.
[0102] In some other embodiments, copper sulfate is dissolved in deionized water at a ratio of 20% or 40% to prepare a chemical plating solution, 20% or 30% zirconium oxide whiskers are added to prepare a composite powder, 60% or 70% of quartz glass powder and 1% or 10% of the composite powder are added to a liquid polyacrylate photocurable resin to obtain a ceramic core slurry, and the magnitude of the magnetic field applied during 3D printing is 1T or 2T, and other values are the same as in Example 1. The above embodiments can also achieve the technical effect that the room temperature and high temperature flexural strength and high temperature creep resistance of the ceramic core are better than those of the comparative example.
[0103] In some other embodiments of preparing ceramic cores, copper sulfate is dissolved in deionized water at a ratio of 20% or 40% to prepare a chemical plating solution, 10% or 20% aluminum oxide whiskers are added to prepare a composite powder, 50% or 70% magnesium oxide powder and 1% or 10% of the composite powder are added to a liquid polyacrylate photocurable resin to obtain a ceramic core slurry, and the magnitude of the magnetic field applied during 3D printing is 0.1T or 2T, and other values are the same as those in Example 2. The above embodiments can also achieve the technical effect that the room temperature and high temperature flexural strength and high temperature creep resistance of the ceramic core are better than those of the comparative example.
[0104] In some other embodiments of preparing ceramic cores, nickel sulfate is dissolved in deionized water at a ratio of 20% or 40% to prepare a chemical plating solution, 20% or 30% silicon carbide whiskers are added to prepare composite powders, 60% or 50% yttrium oxide powder and 5% or 10% composite powders are added to liquid polyacrylate photocurable resin to obtain ceramic core slurry, and the magnitude of the magnetic field applied during 3D printing is 0.1T or 2T, and other values are the same as those in Example 3. The above embodiments can also achieve the technical effect that the room temperature and high temperature flexural strength and high temperature creep resistance of the ceramic core are better than those of the comparative example.
[0105] In some other embodiments of preparing ceramic cores, nickel sulfate is dissolved in deionized water at a ratio of 20% or 30% to prepare a chemical plating solution, 10% or 30% mullite whiskers are added to prepare a composite powder, 50% or 70% of alumina powder and 1% or 5% of the composite powder are added to a liquid polyacrylate photocurable resin to obtain a ceramic core slurry, and the magnitude of the magnetic field applied during 3D printing is 0.1T or 1T, and other values are the same as those in Example 4. The above embodiments can also achieve the technical effect that the room temperature and high temperature flexural strength and high temperature creep resistance of the ceramic core are better than those of the comparative example.
[0106] In some other embodiments of preparing ceramic cores, cobalt sulfate is dissolved in deionized water at a ratio of 20% or 40% to prepare a chemical plating solution, 10% or 30% silicon nitride whiskers are added to prepare a composite powder, 50% or 70% of alumina powder and 1% or 10% of the composite powder are added to a liquid polyacrylate photocurable resin to obtain a ceramic core slurry, and the magnitude of the magnetic field applied during 3D printing is 0.1T or 2T, and other values are the same as those in Example 5. The above embodiments can also achieve the technical effect that the room temperature and high temperature flexural strength and high temperature creep resistance of the ceramic core are better than those of the comparative example.
[0107] In summary, the present invention metallizes ceramic whiskers through a chemical plating process to obtain a ceramic whisker-metal phase composite powder with a core-shell structure, and then in the 3D printing light-curing molding process, a magnetic field is applied to control the orientation of the ceramic whisker-metal phase composite powder with a core-shell structure in the ceramic core slurry, that is, the directional arrangement of the ceramic whiskers, so that the performance of the ceramic core can be controlled, especially the mechanical properties of the thin part of the ceramic core can be improved, and a high-performance ceramic core that meets the requirements can be manufactured. The present invention can also be applied to the development and application of ceramic cores of other systems.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0109] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0110] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
Claims
1. A method for preparing a ceramic core with enhanced whisker orientation, characterized in that: The preparation method comprises the following steps: S1, preparing a composite powder with a core of a ceramic whisker and a shell of a metal phase; S2, mixing refractory powder and composite powder to form ceramic core slurry; S3, using ceramic core slurry to form a ceramic core blank and adjust the powder orientation; S4, embedding the ceramic core blank with powder and then sintering at high temperature to obtain a ceramic core; In step S2, the weight percentage of the refractory powder is 50-70%, and the weight percentage of the composite powder is 1-10%; In step S3, a ceramic core blank is obtained by 3D printing photocuring, and a magnetic field is applied during the 3D printing process; The magnetic field strength of the magnetic field is 0.1-2T.
2. The method for preparing a ceramic core with enhanced whisker orientation according to claim 1, characterized in that In step S1, the ceramic whiskers are metallized, and then a composite powder having a ceramic whisker core and a metal shell is prepared by a chemical plating method.
3. The method for preparing a ceramic core with enhanced whisker orientation according to claim 2, characterized in that In step S1, a chemical plating solution is prepared, and the treated ceramic whiskers are added into the chemical plating solution for ultrasonic chemical plating to obtain a composite powder with a core of a ceramic whisker and a shell of a metal phase.
4. The method for preparing a ceramic core with enhanced whisker orientation according to claim 3, characterized in that: In step S1, a sulfate solution is added to deionized water, and then a reducing agent and a complexing agent are added to obtain a chemical plating solution; The metal element in the sulfate solution is nickel, cobalt or copper, and the added ratio of the sulfate solution is 20-40%; The added amount of the ceramic whisker accounts for 10-30% by weight of the total amount. The ceramic whisker is alumina whisker, zirconia whisker, mullite whisker, silicon nitride whisker or silicon carbide whisker. The diameter of the ceramic whisker is 50-500nm, the length is 1-10μm, and the purity is not less than 90%.
5. The method for preparing a ceramic core with enhanced whisker orientation according to claim 1, characterized in that: In step S2, refractory powder and composite powder are added into the photocurable resin and dispersed uniformly to obtain ceramic core slurry.
6. The method for preparing a ceramic core with enhanced whisker orientation according to claim 5, characterized in that: The refractory material powder is quartz glass powder, alumina powder, magnesium oxide powder, calcium oxide powder or yttrium oxide powder. The particle size of the refractory material powder is 10-40 μm and the purity is not less than 99.90%.
7. The method for preparing a ceramic core with enhanced whisker orientation according to claim 1, characterized in that: The power of the 3D printing light-stereolithography is 5-20 mW / cm 2 The thickness of each layer is 50-500μm, and the exposure time of each layer is 1-10s.
8. The method for preparing a ceramic core with enhanced whisker orientation according to claim 1, characterized in that: In step S3, the magnetic field strength of the magnetic field is 1-2T.
9. The method for preparing a ceramic core with enhanced whisker orientation according to claim 1, characterized in that: In step S4, the final sintering temperature of the high temperature sintering is 1500-1600°C; The heating process of high temperature sintering includes multiple heating stages, the heating range of each heating stage is 400-600°C, the heating rate is 2-8°C / min, and the insulation time after heating in each stage is 2-10h; The multiple heating stages include: the first stage is heating from room temperature to 400°C at a heating rate of 2°C / min, and keeping at 400°C for 3 hours; the second stage is heating from 400°C to a maximum temperature of 900°C at a heating rate of 5°C / min, and keeping at this temperature for 5 hours; the third stage is heating from 900°C to a maximum temperature of 1500°C at a heating rate of 8°C / min, and keeping at this temperature for 10 hours.
10. A whisker-oriented reinforced ceramic core, characterized in that: The ceramic core is prepared using the method for preparing a whisker-oriented enhanced ceramic core as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method for metal-ceramic composite powder of core-shell structure
CN109365802A
Preparing method of orientation arranged ceramic crystal whisker or fiber reinforced non-corrodible steel based material
CN101012537A
Potassium titanate whisker reinforced silicon-based ceramic core 3D printing preparation method
CN112979333A
Silicon carbide whisker oriented reinforced wear-resistant antifriction phosphate ceramic coating and preparation method thereof
CN118515996A
Fiber-reinforced metal matrix composite and manufacturing method therefor
JP2004359990A